Optimizing substrates for Caulerpa racemosa cultivation in Bintan Island, Indonesia - TENGKU SAID RAZA’I; SYAIFULLAH JAMAN; DJAROD SETIAJI; MUHAMMAD HASBY; HILFI PARDI; IMAM PANGESTIANSYAH PUTRA (Society for Indonesian Biodiversity, 2025)
Abstract. Raza’i TS, Jaman S, Setiaji D, Hasby M, Pardi H, Putra IP. 2025. Optimizing substrates for Caulerpa racemosa cultivation in Bintan Island, Indonesia. Biodiversitas 26: 5525-5533. This study aimed to determine the most suitable substrate medium for the cultivation of Caulerpa racemosa and to provide a scientific basis for the development of sustainable aquaculture practices in Bintan Island. An ex-situ experimental method was employed by culturing C. racemosa under different substrate treatments. Growth performance was assessed through several parameters, including total length, stolon length, number of assimilators, assimilator length, and assimilator diameter. Prior to statistical testing, the data were examined for normality and homogeneity of variance, followed by analysis of variance (ANOVA) to evaluate significant differences among treatments. The findings demonstrated that mud was the most effective substrate for C. racemosa culture. On average, cultures grown on mud substrates achieved a total length growth of 57.62 mm/day, stolon length growth of 2.75 mm/day, assimilator length growth of 4.85 mm/day, and assimilator diameter growth of 1.24 mm/day. Statistical analysis confirmed that there were significant differences in growth across the various substrate treatments, highlighting the influence of substrate type on the cultivation success of C. racemosa. Overall, this study concludes that mud represents the optimal substrate medium for the culture of C. racemosa. These results provide important implications for the development of environmentally friendly and sustainable aquaculture systems in Bintan Island. The promotion of C. racemosa as an aquaculture commodity holds strong potential to support local livelihoods and contribute to the economic development of coastal communities in Bintan Island, Indonesia.